Aromatic polyketides from a caterpillar associated Alternaria sp. Issue 31 (2nd August 2017) - Shen, Ye; Xu, Qin Lan; Cheng, Ping; Liu, Cheng Li; Lu, Zhi Yao; Li, Wei; Wang, Ting Ting; Lu, Yan Hua; Tan, Ren Xiang; Ge, Hui Ming; Jiao, Rui Hua
Graphical abstract: Highlights: Five new aromatic polyketides were isolated from a caterpillar associated fungus. We obtained crystals of compound1 and compound3 . Compounds4 and5 showed weak cytotoxic activities. Abstract: Five new aromatic polyketides, alternaphenols A–E (1 –5 ), and two known compounds (6 –7 ) were isolated from a liquid culture of Alternaria sp. (strain no. NF2198), a caterpillar associated fungus. Their structures were determined by extensive spectroscopic analysis and single crystal X-ray crystallography. Compounds1 –7 were evaluated for their cytotoxic activities against a human skin melanoma A-375 cell line. Only compounds4 and5 showed weak cytotoxic activities.